2010
DOI: 10.1152/ajpheart.00763.2009
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 inhibits the in vivo and in vitro adverse effects of TNF-α on the endothelium of murine aorta

Abstract: TNF-α is a proinflammatory cytokine and is an important mediator of maternal endothelial dysfunction leading to preeclampsia. In this study, we tested whether IL-10 protects against TNF-α-induced endothelial dysfunction in murine aorta. In in vitro experiments, aortic rings of C57BL/6 female mice were incubated in Dulbecco's modified Eagle's medium in the presence of either vehicle (distilled H(2)O), TNF-α (4 nmol/l), or recombinant mouse IL-10 (300 ng/ml) or in the presence of both TNF-α and IL-10 for 22 h at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 73 publications
6
35
1
Order By: Relevance
“…18,43 In the UUO model, we found that myogenic activation of Akt upregulated serum levels of stromal cell-derived factor-1, IL-10, and IL-17, which are known to activate eNOS. 44,45 Further studies will be required to determine whether these factors are involved in renal eNOS activation and renoprotective properties of Akt1-mediated skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…18,43 In the UUO model, we found that myogenic activation of Akt upregulated serum levels of stromal cell-derived factor-1, IL-10, and IL-17, which are known to activate eNOS. 44,45 Further studies will be required to determine whether these factors are involved in renal eNOS activation and renoprotective properties of Akt1-mediated skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on mice, the authors reported that IL-10 exerted its antiinflammatory influence by inhibiting the in vivo and in vitro adverse effects of TNF-α on the endothelium of the murine aorta by restoring the eNOS IL-10 and LSS in African American HUVECs -Babbitt et al protein expression that was reduced by TNF-α. 15 This study also showed that IL-10 without the presence of TNF-α had no effect on eNOS expression. 15 An additional study was conducted on HUVECs pre-incubated with TNF-α, and it was demonstrated that eNOS protein expression and NO production were increased in the cells subsequent to incubation with IL-10.…”
Section: Discussionmentioning
confidence: 59%
“…15 This study also showed that IL-10 without the presence of TNF-α had no effect on eNOS expression. 15 An additional study was conducted on HUVECs pre-incubated with TNF-α, and it was demonstrated that eNOS protein expression and NO production were increased in the cells subsequent to incubation with IL-10. 18 The authors concluded that in the presence of a pro-inflammatory stimulus, increased eNOS protein expression was mediated by the anti-inflammatory effect of IL-10.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…(Guyon et al, 2008). Studies have also reported that IL-10 plays an essential role in the suppression of the production of pro-inflammatory cytokines like TNFa (Dhingra et al, 2009) by inhibiting NF-B activity in purified T-lymphocytes (Zemse et al, 2010).…”
Section: Discussionmentioning
confidence: 98%